2020
DOI: 10.1371/journal.pntd.0008175
|View full text |Cite
|
Sign up to set email alerts
|

Field evaluation of DNA detection of human filarial and malaria parasites using mosquito excreta/feces

Abstract: We recently developed a superhydrophobic cone-based method for the collection of mosquito excreta/feces (E/F) for the molecular xenomonitoring of vector-borne parasites showing higher throughput compared to the traditional approach. To test its field applicability, we used this platform to detect the presence of filarial and malaria parasites in two villages of Ghana and compared results to those for detection in mosquito carcasses and human blood. We compared the molecular detection of three parasites (Wucher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…All studies screened mosquito carcasses for filarial DNA. One study additionally reported the prevalence in mosquito excreta/feces [ 31 ]. However, for consistency with the other studies, we only included the mosquito carcass MX rate in our analyses.…”
Section: Resultsmentioning
confidence: 99%
“…All studies screened mosquito carcasses for filarial DNA. One study additionally reported the prevalence in mosquito excreta/feces [ 31 ]. However, for consistency with the other studies, we only included the mosquito carcass MX rate in our analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Attempting to meet this need, we have identified a high copy-number repetitive sequence which we have exploited as a qPCR assay target. Testing this Mp R1 assay against a ribosomal sequence-targeting reference assay [5,26], our index assay demonstrated improved analytical sensitivity, facilitating consistent detection of as little as 10 fg of pathogen-derived gDNA. Moreover, clinical sensitivity was also improved, with additional positive samples identified when testing human blood-derived DNA extracts (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…In order to assess the clinical sensitivity of our newly described repetitive sequence-targeting assay, DNA from 158 dried human blood samples, and 316 individual mosquito samples, previously collected and extracted as part of an unrelated study [26], were tested for the presence of M. perstans using both our index assay, and a previously described, ribosomal sequence-targeting reference assay [5,26]. All samples were tested using each assay's respective optimal conditions, and testing was performed in duplicate.…”
Section: Assessment Of Clinical Sensitivitymentioning
confidence: 99%
“…DNA was then extracted from each sample using the MinElute column procedure (Qiagen, Germantown, MD). Extraction of DNA from mosquito and fly carcasses was conducted using DNeasy extraction kits (Qiagen) with a mechanical disruption stage using a TissueLyser bead mill (Qiagen) as previously described [ 17 ].…”
Section: Methodsmentioning
confidence: 99%